Psychodrama: “ body, space and time towards creative freedom” - Gabriela Severino; Walter Sergio Silva; Mª Florencia Silva Severino (Arteterapia)
Psychodrama, created by Jacob Levy Moreno, is a method of approach to the individual, the family, groups and the community, which had its origins in the theatre, sociology and psychology. From his work with children and marginalized groups, its creator gestated its theory and its technique. It develops in different areas: clinical, psychotherapy, pedagogy and community. The body, the game, the space and the time, converge in a poetic manner and contribute to the creative freedom and so cherished spontaneity. The psychodrama unfolds in this transitional space, which being neither internal nor external, becomes the pluripotent space of infinite creative possibilities